Strategi Peningkatan Kinerja Penyuluh Pertanian di Balai Penyuluh Pertanian (BPP) Tembilahan Kabupaten Indragiri Hilir - Indah Chairunnisa; Partini Partini; Yuslizar Yuslizar (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The transfer of agricultural extension management authority from local governments to the Ministry of Agriculture has necessitated improvements in the capacity and effectiveness of agricultural extension services. This study provides a new perspective on agricultural extension in the post-transition period and its implications for enhancing extension workers' performance. The study aims to analyze the internal and external factors affecting the performance of agricultural extension workers and to formulate strategies to improve their performance at the Tembilahan Agricultural Extension Center (Balai Penyuluhan Pertanian/BPP) in Indragiri Hilir Regency. The research was conducted from January to May 2026 and involved all seven agricultural extension workers assigned to the Tembilahan Agricultural Extension Center (BPP), along with one district working team coordinator, as respondents. The findings indicate that the internal condition of the Tembilahan Agricultural Extension Center is strong, with an Internal Factor Analysis Summary (IFAS) score of 3.55, while its external condition is moderate, with an External Factor Analysis Summary (EFAS) score of 2.20. The strategic position falls within Quadrant I, indicating that the organization possesses sufficient strengths to capitalize on available opportunities. The priority strategies recommended include optimizing extension programs to meet farmers' needs, enhancing extension workers' competencies through Training of Trainers (ToT) programs, strengthening partnerships with farmers, and improving work motivation by providing incentives and awards